"The Role of E-government in Activating Knowledge Management To Raise the Efficiency of Government Performance in Egypt: Challenges and Axes of Reform" - Aly, Wael (The Arab Journal of Administration, 2022)
The modern applications of e-government in most countries of the world - whether developing or developed - have contributed to rationalizing and improving the cost and quality of government services provided to citizens and businessmen. This tangible improvement in the level of services and the degree of satisfaction of the recipients of these services has encouraged countries to try to expand the dissemination and application of e-government programs and projects. But the expansion of the adoption of the e-government system, especially in the developing world - such as the Egyptian case - is faced by many challenges and obstacles such as the required technology and infrastructure, the appropriateness of the legislative framework and the organizational and administrative structure, as well as the prevailing organizational and societal culture. In order to adopt an effective e-government system, it is necessary for governments to adopt an integrated strategy to overcome these challenges in order to implement effective e-government programs. The success of the e-government system requires reengineering the government services package and rationalizing the standardizing procedures for its application. Based on that, the knowledge acquired by government employees must play an important role in understanding these procedures and their successful implementation. But the latent civil servants have that knowledge and have run it for decades, through a stubborn bureaucracy, vehemently resisting any attempt to impart and share knowledge for fear of losing part of their power and influence in the bureaucratic organization. This dilemma requires a conscious government effort to overcome it, by adopting effective incentive and reward systems to convince the public employee of the importance of adopting and implementing e-government, which requires activating knowledge management and for employees to share knowledge related to their work and experiences, in pursuit of developing and improving public services, and raising performance efficiency. The government supports community governance, and seeks to achieve the desired sustainable development goals. Thus, through this research paper, the researcher will shed light on the concept of e-government and the elements of its application. It will also deal with the concept of knowledge management and the mechanisms of knowledge sharing, with an attempt to develop a proposed framework to demonstrate the relationship between the application of the e-government system, the activation of knowledge management and raising the efficiency of government performance. Finally, to identify the challenges facing the implementation of an effective e-government program in Egypt, with a statement of the reform axes that are required to be met to confront these challenges.